Improving Knowledge in Malay Weaving Business Groups Regarding The Making of Natural Fabric Dye Paste: Peningkatan Pengetahuan Pada Kelompok Usaha Tenun Melayu Mengenai Pembuatan Pasta Pewarna Kain Alami - Risnasari, Iwan; Nazliniwaty, Nazliniwaty; Nabiilah, Putri; Ismanelly Hanum, Tengku; Anjelisa Zaitun Hasibuan, Poppy; Aulia Rahma, Annisa (Universitas Haji Sumatera Utara, 2025)
The demand for songket cloth has increased since the regulation on the use of traditional clothing in every government agency on certain days. The increasing need for songket cloth has encouraged people who make a living as cloth weavers in Bandar Khalipah Village to produce songket cloth with various colour variants. However, most of the songket fabrics produced use synthetic dyes that have a negative impact on the environment and human health. Therefore, the weaving community needs to get education related to the use of natural materials as yarn dyes to support the production of songket fabrics that are environmentally friendly and of high selling value. Therefore, the community service team is interested in conducting community service to the Songket Fabric weavers of Bandar Khalipah Village by providing skills training on making natural fabric dye paste preparations. Community service activities carried out at the Malay Weaving Joint Business Group in Bandar Khalipah, Deli Serdang in the form of providing education related to natural dyes and production techniques for dye paste preparations from turmeric rhizomes and merbau wood. In addition, materials on business management and product marketing were also provided. This activity ended with a survey and hedonic test of the product. This is also intended to help songket cloth weavers get natural dye preparations that are stable and easy to use. Furthermore, it is hoped that partners can create more creative songket fabric products using natural dyes. The results of the survey analysis showed that the service activities provided an increase from 44% to 88% of the participants' knowledge related to the activity material.